Peran Guru PAI dalam Mengatai Kenakalan Siswa Sekolah Menengah Pertama - Layyinawati, Rahmi Rizqina; Haryanto, Budi; Pujiastutik, Anita (Universitas Batanghari Jambi, 2024)
Junior high school students are entering a transitional age or puberty which causes them to be in a state of needing recognition and searching for identity so that they are very vulnerable to environmental influences. This causes the risk of juvenile delinquency. PAI (islamic religion) teachers have a very important role to provide religious and spiritual guidance for students to build character and morals. This research was conducted at SMPN 5 Sidoarjo. The method used is qualitative with a naturalistic positivistic approach with data collection techniques through interviews, documentation and literature review. The results of this study are that the form of juvenile delinquency in SMPN 5 Sidoarjo students is classified as low delinquency. PAI teachers have contributed and played a major role in handling student delinquency, namely carrying out spiritual guidance programs on a scheduled basis. The supporting factors are students with Islamic religion being the majority and the inhibiting factors are carelessness in supervision and differences in student character.